Development of An Android-Based Physics E-Book with A Scientific Approach to Improve The Learning Outcomes of Class X High School Students on Impulse and Momentum Materials - Ndoa, Y A A; Anastasia, D P; Jumadi, J (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
The use of technology during a pandemic can be in the form of using e-books in learning activities. This research is Research and Development (RD) which produces a product in the form of an Android-based physics e-book with a scientific approach. The aim of this study is to develop and determine the feasibility and effectiveness of e-books in improving learning outcomes on impulse and momentum materials. The development of this physics e-book uses a 4D model according to Thiagarajan, namely define, design, develop, and deploy. Results based on 4D model steps are (1) Define to produce an analysis of the needs of students during online learning, (2) Design to produce a product, namely a physics e-book, and (3) Develop to produce validation and the final product, and (4) Deploy of products is distributed in a limited way to physics teachers in Jatinom Senior High School. Based on expert consideration, the average product feasibility on aspects of material/content, language and images, e-book content design, and language included in the very high category. The physics e-book applied to students class X Mathematics and Natural Sciences in Jatinom Senior High School. Student learning outcomes increased in the moderate category after carrying out physics learning with e-books. Thus, an Android-based physics e-book with a scientific approach is feasible and efficient to be applied in physics learning on impulse and momentum material to improve student learning outcomes.